The toxicity of glyphosate alone and glyphosate–surfactant mixtures to western toad (Anaxyrus boreas) tadpoles. (29th October 2015) - Vincent, Kim; Davidson, Carlos
Abstract: Pesticide choice based on toxicity to nontarget wildlife is reliant on available toxicity data. Despite a number of recent studies examining the effects of glyphosate on amphibians, very few have aimed to understand the toxicological effects of glyphosate in combination with surfactants as it is commonly applied in the field. Land managers interested in making pesticide choices based on minimizing impacts to nontarget wildlife are hindered by a lack of published toxicity data. Short‐term acute toxicity trials were conducted for glyphosate in the form of isopropylamine salt (IPA) alone and mixed with 2 surfactants: Agri‐dex and Competitor with western toad ( Anaxyrus [ Bufo ] boreas ) tadpoles. Glyphosate IPA mixed with Competitor was 6 times more toxic than glyphosate IPA mixed with Agri‐dex, and both mixtures were more toxic than glyphosate IPA alone. The median lethal concentrations reported for 24‐h and 48‐h exposures were 8279 mg/L (24 h) and 6392 mg/L (48 h) for glyphosate IPA alone; 5092 mg/L (24 h) and 4254 mg/L (48 h) for glyphosate IPA mixed with Agri‐dex; and 853 mg/L (24 h) and 711 mg/L (48 h) for glyphosate IPA mixed with Competitor. The present study indicates that the toxicity of a tank mix may be greatly increased by the addition of surfactants and may vary widely depending on the specific surfactant. Environ Toxicol Chem 2015;34:2791–2795. © 2015 SETAC